Efficiency and Ship Class of Shipping Companies: The Case of Greek-owned Shipping Companies - Mantalis, George; Garefalakis, Alexandros; Lemonakis, Christos; Vassakis, Konstantinos; Xanthos, George (International Journal of Supply Chain Management, 2016)
Transport industry is a very importantfactor for country’s development in various fields.One of them is economic, since the development oftransport reinforces the trade relationships betweencountries and companies. This helps countries andfirms to utilize the competitive advantage which mayhave. Therefore, the volume of transport carried outby countries could reflect their growth. This studyaims to examine the efficiency (by ship class) ofGreek-owed shipping companies, listed on New Yorkstock markets. The analysis was performed via BCCmodel of Data Envelopment Analysis (inputsorientation).